The effect of phase state on damping capacity in Ti-5Al-5Mo-5V - Ryumshyna, T.; Nosolev, I.; Konstantinova, T. (Functional Materials, 2005)
The internal friction and Young's modulus behavior at function temperature in the
range from 78 К to 300 К were studied in Ti-5Al-5Mo-5V alloy. The changing of quenching temperature regulated the phase composition. The internal friction peaks at 140-160 К were observed. The peak parameters were found to be sensitive to phase composition. The nature of maxima was discussed. The significant decrease of Young's modulus
was observed in monophase β alloy after quenching at temperature 900℃. Исследовано влияние фазового состава Ti-5Al-5Mo-5V сплава на температурные зависимости внутреннего трения и модуля Юнга в диапазоне 78-300 К. Фазовый состав сплава регулировался путем изменения температуры нагрева под закалку. Установлено существование максимума при 140-160 К, параметры которого зависят от фазового состава сплава. Проведен анализ процессов, отвечающих за формирование пика. Обнаружено значительное снижение модуля в однофазном β-сплаве после закалки от 900℃. Вивчено вплив фазового складу сплаву Ti-5Al-5Mo-5V на температурнi залежностi внутрiшнього тертя та модуля Юнга у дiапазонi 78-300 К. Фазовий склад сплаву регулювався змiною температури нагрiвання пiд загартовування. Установлено iснування максимуму внутрiшнього тертя при 140-160 К, параметри якого залежать вiд фазового складу сплаву. Проведено аналiз процесiв, якi вiдповiдають за формування пiку. Виявлено значне зниження модуля в однофазному β-сплавi пiсля гартування вiд 900℃.